The Implementation of The Rights of The Child in The United States - Tehnee Bennett (Universitas Internasional Batam, 2017)
Early 20th century- U.S. courts began to give children some form of legal protection, most notably in custody hearings. From the 1960s, children began to earn participatory rights of their own. The trend for recognizing children's rights reversed in the 1990s amid an increase in juvenile crime. With a rise in juvenile crime in the 1990s, parents felt the need to be more in control of a child's upbringing in order to raise more morally-sound and law-abiding citizens. This trend in parenting grew from the family values movement of the 1980s. The U.S. has yet to ratify the Convention on the Rights of the Child (CRC) is quite perplexing, particularly in light of the crucial role its UN delegates played in structuring the CRC in the 1980s. The U.S. has, however, signed the CRC in 1995 and ratified the Optional Protocols on the involvement of children in armed conflict and the Optional Protocol on the sale of children. Since the sign of the CRC in 1995, several states recognized the need for such an amendment protecting the rights of parents to raise their child as they see fit. In 1996, Colorado was the first state to propose an amendment to its state constitution. While voters rejected the amendment, socially conservative politicians continued their fight against the CRC. Peter Hoekstra introduced a parental rights amendment for the U.S. Constitution in the summer of 2008. In 2009 Hoekstra again proposed a constitutional amendment supporting the rights of parents with Senate co-sponsor Jim DeMint. The CRC is a human rights treaty, which is classified as “not self-executing, therefore even if the CRC is ratified, individual states can propose amendments to their state constitution that will grant their desired parental right. === Di awal abad ke 20, Pengadilan Amerika Serikat mulia meberikan beberapa bentuk perlindungan hukum kepada anak-anak. Sejak tahun 1960-an, anak mulai memperoleh hak untuk berpartisipasi. Trend terhadap pengakuan hak anak di tahun 1990-an sebaliknya meningkatkan jumlah kejahatan anak. Dengan peningkatan jumlah kejahatan anak di tahun 1990-an, orang tua merasa perlu untuk lebih mengawasi cara membesarkan anak agar menjadi warga masyarakat yang bermoral dan patuh terhadap hukum. Trend dalam pengasuhan anak bertumbuh dari gerakan nilai-nilai keluarga di tahun 1980-an. Amerika Serikat yang belum meratifikasi Konvensi Hak Anak cukup membingungkan, khususnya dikarenakan peranan penting delegasinya pada Perserikatan Bangsa-Bangsa (PBB) dalam menyusun Konvensi Anak di tahun 1980-an. Namun demikian, AS telah menandatangani Konvensi Anak di tahun 1995 dan meratifikasi Protokol Tambahan tentang Keterlibatan Anaka Dalam Konflik Bersenjata. Sejak penandatanganan Konvensi Hak Anak di tahun 1995, beberapa negara bagian mengakui perlunya perubahan terhadap perlindungan hak orang dalam membesarkan anak mereka. Pada tahun 1996, Colorado merupakan negara bagian pertama yang merubah Undang-Undang Dasar Negara Bagiannya. Pemilih menolak perubahan tersebut, politisi konservatif melanjutkan perlawanan terhadap Konvensi Hak Anak. Peter Hoekstra memperkenalkan perubahan hak orang tua untuk Konstitusi AS pada musim panas tahun 2008. Pada tahun 2009, Hoekstra kembali mengusulkan perubahan konstitusi yang mendukung hak orang tua kepada Penyokong Senat dengan Jim DeMint. Konvensi Anak merupakan penjanjian internasional terkait hak asasi manusia yang digolongkan sebagai “not self-executing”, oleh karena itu meskipun Konvensi Anak diratifikasi, tiap negara bagian dapat mengusulkan perubahan terhadap konstitusi mereka yang memberikan hak orang tua yang diinginkan.